STRATEGI COMMUNITY-BASED MANAGEMENT UNTUK OPTIMALISASI PENAMPUNGAN DAN DISTRIBUSI IKAN STUDI PADA BUMDES PESONA BENGARA - Wahyudi, Wahyudi; Rosmayati, Siti (JURNAL EKOBIS DEWANTARA, 2025)
Efficient management of fish stocking and distribution is a key challenge in supporting the sustainability of the fisheries sector, especially in rural areas. This research explores the community-based management (CBM) strategy in the Pesona Bengara Village-Owned Enterprise (BUMDes) study in optimizing the fish stocking and distribution process involving active participation of local communities, utilization of simple technology, and strengthening village institutions to improve efficiency and economic welfare. The study used qualitative methods with in-depth interviews, participatory observation, and document analysis. The results show that the CBM approach increases community involvement in the fisheries supply chain through the joint management of holding facilities and the implementation of distribution systems. In addition, collaboration with external parties such as other vendors and local government also supported the success of this strategy. The implications of this research emphasize the importance of local community empowerment in creating sustainable business models that are responsive to community needs and contribute to the development of adaptive and inclusive village-based fisheries policies. As such, the CBM strategy has proven effective in creating added value for village economies while maintaining the sustainability of fish resources.